Analysis of Science Learnin Based on The Merdeka Curriculum - Efi, Nurul; Sholichaty, Chomsy; Setiawati, Dian Agustin; Wardani, Herni Ika; Suminto, Bambang; Fatimah, Siti (Proceeding International Conference on Religion, Science and Education, 2025)
This study aims to analyze the implementation of Science (IPA) learning in the context of the Merdeka Curriculum applied in Indonesia. The Merdeka Curriculum provides greater freedom for schools and teachers in designing learning processes that focus on developing students’ potential, such as critical thinking, creativity, and collaboration skills. In Science learning, project-based approaches, formative assessments, and the use of real-life contexts are key aspects explored. Through a qualitative method, data were collected from observations, interviews, and document analysis at several schools that have implemented the Merdeka Curriculum. The results show that the Merdeka Curriculum opens up opportunities for more flexible and relevant learning, but challenges related to teacher readiness, infrastructure, and resource support remain obstacles. Therefore, further development is needed in teacher training and the provision of facilities and infrastructure to maximize the potential of the Merdeka Curriculum in Science learning.